2020
DOI: 10.5334/oq.71
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA Research in Maritime and Underwater Archaeology: Pitfalls, Promise, and Future Directions

Abstract: The rapid progression of DNA technology allows for the application of recently developed techniques to an ever-growing body of archaeological and environmental material recovered from submerged archaeological sites. As NGS and DNA Capture replace PCR as the predominant method used to characterise DNA present within an archaeological sample, it is necessary to consider how this effects the possibilities for future research, but also gives cause to reconsider the findings of previously published work from PCR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
(150 reference statements)
0
9
0
Order By: Relevance
“…In order to strengthen the interpretation and the identification of grapevine products by ruling out contamination, in each context we also analysed vessels that are not supposed to have been in contact with wine. Analysis of vessels assumed to have contained 'other commodities' ensures that the small and highly labile organic acids found in grapevine products are specific to certain vessels and therefore not the result of contamination (Drieu et al, 2020), while the inclusion of environmental samples of soil and seafloor sediment can help to establish what molecules are naturally present in the deposition environment (Briggs, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In order to strengthen the interpretation and the identification of grapevine products by ruling out contamination, in each context we also analysed vessels that are not supposed to have been in contact with wine. Analysis of vessels assumed to have contained 'other commodities' ensures that the small and highly labile organic acids found in grapevine products are specific to certain vessels and therefore not the result of contamination (Drieu et al, 2020), while the inclusion of environmental samples of soil and seafloor sediment can help to establish what molecules are naturally present in the deposition environment (Briggs, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long exposure to degradation under oxic conditions during transport in the water column, and substantially lower concentration of organic matter on the seafloor, there is evidence that planktonic eDNA is preserved in marine sediments and contains exploitable ecological signal 8 . Earlier studies have shown sedaDNA preservation in marine sediments deposited under anoxia with unusually high amounts of organic matter preserved 9 , but later investigations indicate that sedaDNA can also be extracted from normal marine sediments, dominated by clastic or biogenic mineral fractions [10][11][12] .…”
mentioning
confidence: 99%
“…Earlier studies have shown sedaDNA preservation in marine sediments deposited under anoxia with unusually high amounts of organic matter preserved 9 , but later investigations indicate that sedaDNA can also be extracted from normal marine sediments, dominated by clastic or biogenic mineral fractions [10][11][12] . In addition, the low temperature of deep-sea water (0-4 °C) ensures a good preservation of sedaDNA 7,8 . Using planktonic foraminifera as a "Rosetta Stone", allowing benchmarking of sedaDNA signatures by co-occurring fossil tests of these organisms, Morard et al (2017) 9 showed that the fingerprint of plankton eDNA arriving on the seafloor preserves the ecological signature of these organisms at a large geographic scale.…”
mentioning
confidence: 99%
“…Topics related to past aquatic environments include ecological reconstructions via plant metabarcoding [247], past fish population dynamics [248] and the spread and ecological effects of invasive species [249]. A methodological innovation is the use of DNA analysis in (geo)archaeological and historical contexts [245,250,251]. An established approach that holds promise for further development is the reconstruction of traded species provenances and trading networks through DNA analyses of ancient fish remains [252].…”
Section: Progression Of Dna Technologymentioning
confidence: 99%